Micromagnetic modelling and imaging of vortex/merons structures in an oxide | metal heterostructure - Radaelli, PG; Radaelli, J; Waterfield-Price, N; Johnson, RD (American Physical Society, 2020)
Using micromagnetic simulations, we have modelled the formation of imprinted merons and anti-merons in cobalt overlayers of different thickness (1-8 nm), stabilised by interfacial exchange with antiferromagnetic vortices in $α$-Fe2O3. Structures similar to those observed experimentally could be obtained with reasonable exchange parameters, also in the presence of surface roughness. We produce simulated meron/antimeron images by magnetic force microscopy (MFM) and nitrogen-vacancy (N-V) centre microscopy, and established signatures of these topological structures in different experimental configurations.